Anoikis Mediators in Oral Squamous Cell Carcinoma - Bunek, Julius (2010)
Anoikis—apoptotic cell death triggered by loss of extracellular matrix (ECM) contacts— is dysregulated in many chronic debilitating and fatal diseases. Mechanisms rendering tumor cells resistant to anoikis, although not completely understood, possess significant therapeutic promise. In death receptor-mediated anoikis mechanisms, FAK and RIP dissociate, leading to association of RIP with Fas, formation of the death-inducing signaling complex (DISC), activation of caspase-3, and propagation of anoikis. In contrast, anoikis resistance is accomplished through constitutive activation of survival pathways that include integrin-dependent activation of focal adhesion kinase (FAK) and extracellular-signal-regulated kinase (ERK). In addition, FAK and receptor-interacting protein (RIP) association confers anoikis resistance by inhibiting the association of RIP with Fas and formation of the death signaling complex, which allows cells to escape anoikis. Up-regulation of CD44 also contributes to survival signals and promotes anoikis resistance. This review will focus on the roles of death receptors, pro-survival pathways, and the molecular players involved in anoikis escalation and resistance in OSCC.